2013
DOI: 10.1111/chd.12150
|View full text |Cite
|
Sign up to set email alerts
|

Style of Coping and Its Determinants in Adults with Congenital Heart Disease in a Developing Country

Abstract: The adults with congenital heart disease coped as well as adults without congenital heart disease. Marital status, parenthood, annual income, financial strain, psychological adjustment, and perceived social support were important explanatory factors in adopting a certain style of coping among adults with congenital heart disease. However, longitudinal studies with repeated measures are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 33 publications
1
13
2
Order By: Relevance
“…Consistent with the literature [35][36][37][38][39], women more often used 'social support' , including spirituality and religion, and emotional-focused strategies, including 'avoidance' and 'positive thinking' , than men. Previous studies showed that the educational level and professional status might be associated with some specific coping strategies [40][41][42]. Associations between coping strategies and quality of life were elsewhere documented in other pathologic contexts [33,43].…”
Section: Discussionmentioning
confidence: 94%
“…Consistent with the literature [35][36][37][38][39], women more often used 'social support' , including spirituality and religion, and emotional-focused strategies, including 'avoidance' and 'positive thinking' , than men. Previous studies showed that the educational level and professional status might be associated with some specific coping strategies [40][41][42]. Associations between coping strategies and quality of life were elsewhere documented in other pathologic contexts [33,43].…”
Section: Discussionmentioning
confidence: 94%
“…Consistent with the literature [35–39], women more often used ‘social support’, including spirituality and religion, and emotional-focused strategies, including ‘avoidance’ and ‘positive thinking’, than men. Previous studies showed that the educational level and professional status might be associated with some specific coping strategies [4042]. Associations between coping strategies and quality of life were elsewhere documented in other pathologic contexts [33, 43].…”
Section: Discussionmentioning
confidence: 97%
“…In a large cohort of children with single ventricle, McCrindle et al showed that a lower family income had a negative impact on both physical and psychosocial QoL scores [27]. A low socioeconomic status among CHD adults has also been recently found to be associated with exercise intolerance [11] and ''avoidance behavior'' coping strategy [12]. Therefore, caregivers should consider this financial aspect in the follow-up of patients with CHD, even in pediatric age.…”
Section: Self-reports (Kidscreen-52)mentioning
confidence: 99%